Sardanapal(l)us in Cicero and Philodemus’ On Rhetoric Book 3 - Avdoulou, Eleni (Hyperboreus, 2025)
The present article examines a reference to the Assyrian king Sardanapal(l)us as a builder of Anchiale and Tarsos in Philodemus’ third book On Rhetoric. The name of Themistocles, possibly as a builder of Athenian walls, can be restored in the same passage. This restoration is backed up by a reference to both Sardanapal(l)us and Themistocles in Cicero’s Letters to Atticus (10. 8), a work that contains Philodemean echoes, as already noted by D. Delattre. However, while Sardanapal(l)us is typically mentioned with negative connotations in Cicero, I argue that, considering the context of the third book of On Rhetoric, Philodemus might have credited Sardanapal(l)us, and possibly also Themistocles, for their efforts in protecting their cities. Furthermore, I criticize M. Schneider’s thesis that the different spellings of Sardanapal(l)us may suggest the existence of more than one Sardanapal(l)i.